Ghana : Women's Energy Enterprise - Developing a Model for Mainstreaming Gender into Modern Energy Service Delivery - Kumasi Institute of Technology and Environment (World Bank, Washington, DC, 2014)
This paper looks at the feasibility of creating employment in the energy sector for women in rural communities in Ghana. The report is based on a stakeholders' analysis of the feasibility of embarking on a micro-enterprise on multiple energy services for women in rural fishing and farming communities. The objective of the study is to test a business model for empowering women through income generation in energy service delivery. It is based on the background experience of a successful pilot project, in Bangladesh. The model involves capacity-building among rural women and micro-enterprise development for modern energy service delivery to their communities and surrounding ones. The focus of this study is to see if transfer of skills for manufacturing and production of energy service appliances can be accomplished without a high level of education among rural women. Such skills are considered as opportunities for initiating social transformation. The stakeholders' analysis in five selected communities was carried out to assess the willingness and preparedness of women in these communities to engage in other similar projects in Ghana. The findings of the analysis have recommended that the Nyanyano region be selected as the pilot electrified community. The findings are presented in the report and are followed up with some recommendations on how to proceed and what the next steps should be.